Epistemologia da Educação: a Reprodutibilidade, a Aprendizagem e a Dispersão como elementos de cientificidade - Rodrigues, Marcus Rafael (Universidade Federal de São Carlos, 2024)
The doctoral thesis presented here is the result of reflective and investigative research and development by the Postgraduate Program in Education at UFSCar-Sorocaba and, more specifically, by the Study and Research Group in Education and Epistemology (GEPEE). Considering the recent context of denial, on the part of common sense, as well as, due to the academic debate regarding the epistemic status of education in its consideration as science, the present text has as its starting point and triggering problem, the reflection on the question: is it possible to say that education is a science? And, as a result of this reflection, one can add to the question: what are the factors that corroborate or disqualify it? Having as an investigative horizon the conceptual search that highlights or brings to light the debates on this academic investigation, the method adopted for this purpose was the bibliographical review that took place through the historical framework that spanned classical authors such as Plato, Aristotle, Marx, Comte, to modern and contemporary thinkers such as Kuhn, Popper, Lakatos, and Feyerabend; However, in an attempt to answer the questions as evidence of the opinion that confirms education as a science, Alejandro Ramirez Figueroa and Ferdinand Röhr with the concepts of Network Dispersion and the definition of an object specific to the science of education, translated into the educator triad, educating, and educational task, respectively collaborate directly with the proposed intent. It intends to contribute to the deepening and consolidation of understanding, or even the resumption of reflection on the epistemic relevance of education, that is, deal with the scientific nature of education as the access and maintenance of valid knowledge, to achieve this goal, it presents, through academic, philosophical, and sociological literature, pathways and topics that facilitate such understanding and delineation.
Epistemology of Education: Reproducibility, Learning and Dispersion as elements of scientificity
Keywords: Educação; Education; Epistemologia; Reprodutibilidade; Aprendizagem; Dispersão; Ciência; Epistemology; Reproducibility; Learning; Dispersion; Science; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::FILOSOFIA; CIENCIAS HUMANAS; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO